2019
DOI: 10.3390/cancers11091249
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of HLA Class I Antigens in the Glycolytic Metabolism and Motility of Melanoma Cells

Abstract: Besides playing a crucial role in immune surveillance, human leukocyte antigens (HLA) possess numerous non-immune functions involved in cell communication. In the present study, screening of a panel of HLA class I- and HLA class II-specific monoclonal antibodies (mAbs) for their effects on the metabolism of human melanoma cells showed for the first time that the HLA-B,C-specific mAb B1.23.2 reduced the expression level of key glycolytic enzymes, but did not affect that of mitochondrial respiration effectors. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…In any case, this model can be used to predict physiological outcomes of the cis-association between cell surface open MHC-I conformers and the IR, among other hormone and growth factor receptors (see Box 1). In this respect, and in agreement with some of the above-referenced reports, it is worth mentioning a recent study showing that antibodies against cell surface open HLA-I conformers interfere with the glycolytic metabolism and motility in melanoma cells [132], reinforcing once more the non-immunological functions played by the open MHC-I conformers.…”
Section: Forward-looking Perspectivesupporting
confidence: 86%
“…In any case, this model can be used to predict physiological outcomes of the cis-association between cell surface open MHC-I conformers and the IR, among other hormone and growth factor receptors (see Box 1). In this respect, and in agreement with some of the above-referenced reports, it is worth mentioning a recent study showing that antibodies against cell surface open HLA-I conformers interfere with the glycolytic metabolism and motility in melanoma cells [132], reinforcing once more the non-immunological functions played by the open MHC-I conformers.…”
Section: Forward-looking Perspectivesupporting
confidence: 86%
“…It has also been shown that B2M, a molecule of the MHC-I pathway found to be upregulated in our study, is required for the development of astrogliosis in vitro [ 55 ]. Furthermore, a recent study indicated that besides playing a role in the immune response, HLA class I antigens, and in particular HLA-B and C, are crucial in the metabolism of melanoma cells, sustaining glycolysis [ 56 ]. In light of these published data, it could be hypothesized that the MHC class I pathway is involved in the development of astrogliosis and in the increased glycolysis we observed in this study, and in the potential ability of these human astrocytes to activate microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Seahorse analysis has been performed as previously described [51]. The extracellular acidification rate (ECAR) and the Oxygen Consumption Rate (OCR) were determined using the Seahorse XF96 Extracellular Flux Analyzer (Seahorse Bioscience, Billerica, MA, USA) through Seahorse XF Glycolysis Stress Test Kit (Agilent Technologies, Santa Clara, CA, USA), measuring preferentially the glycolytic function in cells, or Seahorse XF Mito Stress Test Kit (Agilent Technologies), measuring the dependence of cells on the oxidative metabolism.…”
Section: Seahorse Analysismentioning
confidence: 99%
“…cDNAwas obtained by incubating 2 µg of total RNA with 4 U/µL of M-MLV reverse transcriptase (Promega, San Luis Obispo, CA, USA) according to the manufacturer's instructions. Quantitative real time PCR (qPCR) was performed as reported in [51] using the GoTaq ® Probe Systems (Promega). The qPCR analysis was carried out in triplicate using an Applied Biosystems 7500 Sequence Detector with the default PCR setting: 40 cycles at 95 • C for 15 s, 60 • C for 60 s. mRNA was quantified with the DDCt method as described [52].…”
Section: Rna Isolation and Quantitative Pcr (Qpcr)mentioning
confidence: 99%